Electrochemical Determination of Ampicillin Based on an Electropolymerized Poly(o-Phenylenediamine)/Gold Nanoparticle/Single-Walled Carbon Nanotube Modified Glassy Carbon Electrode - Shi, Xiaohong; Ren, Xuehong; Jing, Ning; Zhang, Jialin (Analytical letters, 2020)
A sensitive and selective molecular-imprinted electrochemical sensor was developed for the determination of ampicillin. The molecularly imprinted film was electropolymerized on the surface of a glassy carbon electrode modified with gold nanoparticles (AuNPs) and single walled carbon nanotubes (SWCNTs) using ampicillin as the template molecule and o-phenylendiamine as the functional monomer. Under the optimized conditions, the current change of this electrode showed a linear relationship with the ampicillin concentration from 5.0 × 10 −8 mol/L to 1.0 × 10 −5 mol/L and a detection limit of 1.0 × 10 −9 mol/L. Due to the increased specific surface areas and conductivity of the AuNPs and SWCNTs, this sensor exhibited excellent sensitivity for ampicillin. The recovery values for ampicillin detection in milk using the developed sensor were from 95.0% to 98.1%.